Executive Committee Minutes 2013-01-17 - Academic Senate:::::::::
Agenda approved. Minutes of 10/18; 11/1; 11/15 and 12/6 approved. Chair Report. President Report. Posthumous BA Degree Request for Laura Ivarami approved for Senate consent calendar. Course Instructional Materials Adoption Policy referred to APC, EPC and SAC. Provost Report. Discussion of Resolutions from the Statewide Senate Chair. Vice Chair Report. FSAC Report. Associated Students Report. Faculty eligible for Emeritus Status approved for Senate consent calendar. Senate agenda approved.